Penerapan Metode Tamyiz Dalam Meningkatkan Menerjemah Al-Quran di Sekolah SMK Informatika Utama Krukut Depok - Eva Siti Faridah; Shofwatun Nida; Zaeni Dahlan; Ernawati Ernawati (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
This Islamic education is taught by parents to children from the Koran. Because the Qur'an is a symbol of the very essence of Islamic teachings, the Qur'an was revealed by means of the Arabic language so that it is known that Arabic is the only wasilah for understanding the Qur'an and Sunnah. In understanding the contents of the Koran we must be able to know the translation of the Koran. The Tamyiz method is a practical and easy way to understand Arabic with the specific purpose of translating the Quran. The purpose of this study is to find out the systematic improvement of the translation of the Qur'an after the implementation of the Tamyiz Method. The research was conducted in class XII B with a total of 29 students. Data analysis used in this study used two types of data, namely; 1.) Quantitative Data Analysis is used to answer research problems related to data in the form of numbers and statistical programs. 2.) Qualitative Data Analysis is made to describe, describe and determine the improvement of the learning process, especially the various actions taken by the teacher. The results of this study indicate that the study of the application of the tamyiz method in learning to translate the Koran at SMK Informatika Utama Krukut increased. The increase in learning after the application of the Tamyiz Method, from pre-cycle by 68%, increased in the first cycle by 75.09% and in the second cycle to 81.15%. Keywords: Al-Quran Translation, Tamyiz Method, Islamic Religious Education